MORAL VALUE VIOLATIONS IN AN AMERICAN TRAGEDY NOVEL BY THEODORE DREISER (A Study of Psychoanalisis) - Muhammad Briyan Agunginardi; Aceng Rahmat; Fahrur Rozi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
ABSTRACT This research is a qualitative research. The technique is content analysis using the data in the form of words, phrases, and sentences. Writer uses a psychoanalysis study. In revealing moral values infringement, writer focuses on three questions; how are the type, cause, and effect of moral values violations in the story. Based on psychoanalysis, there is a moral value infringement. The type of moral values infringement is a murdering case. The cause of moral values violations is a self ambition to reach wealth and prosperity. The effect of moral values violations is a charge of death sentence. Based on the research, there are practical implications in education; to improve the quality and quantity of literature learning in high schools in accordance with the objectives contained in the curriculum. Teachers invites the students to enjoy literature study to differ on good and bad moral teachings and to enhance their ability in using English. Keywords: Moral, psychoanalisis, novel